The localization of centromere protein A is conserved among tissues - Eleonora Cappelletti; Francesca M. Piras; Lorenzo Sola; Marco Santagostino; Jessica L. Petersen; Rebecca R. Bellone; Carrie J. Finno; Sichong Peng; Ted S. Kalbfleisch; Ernest Bailey; Solomon G. Nergadze; Elena Giulotto (Communications Biology, 2023)
Abstract Centromeres are epigenetically specified by the histone H3 variant CENP-A. Although mammalian centromeres are typically associated with satellite DNA, we previously demonstrated that the centromere of horse chromosome 11 (ECA11) is completely devoid of satellite DNA. We also showed that the localization of its CENP-A binding domain is not fixed but slides within an about 500 kb region in different individuals, giving rise to positional alleles. These epialleles are inherited as Mendelian traits but their position can move in one generation. It is still unknown whether centromere sliding occurs during meiosis or during development. Here, we first improve the sequence of the ECA11 centromeric region in the EquCab3.0 assembly. Then, to test whether centromere sliding may occur during development, we map the CENP-A binding domains of ECA11 using ChIP-seq in five tissues of different embryonic origin from the four horses of the equine FAANG (Functional Annotation of ANimal Genomes) consortium. Our results demonstrate that the centromere is localized in the same region in all tissues, suggesting that the position of the centromeric domain is maintained during development.